Pengembangan Aplikasi Pembelajaran Membaca Aksara Jawa Menggunakan Speech Recognition (Studi Kasus : SDN Tulusrejo 1 Malang) - Mohamad Ilham; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Javanese have a unique writing culture called Javanese script or hanacaraka. However, few Indonesian people, especially the Javanese who know and can read Javanese script. The role of the East Java Provincial Government is to establish Javanese subjects that will be used as local content subjects in madrasas and schools to preserve them based on the East Java Provincial Governor Regulation number 19 in 2014. In this study developing applications for learning to read Javanese script using speech recognition that is implemented on smartphones that utilize the Android speech recognition library that functions to convert sound into text. SDLC prototyping will be used in the development of the application. Then the features available in the application are learning and training features so students can know and be able to read Javanese script. The results of validation testing are that all system requirements are in accordance with functional requirements. Then in accuracy testing the system gets a value of 85% which means the answer will be the picture that was tested on the problem in accordance with the Javanese script material. In usability testing, the average value of testing is 71.79, which means that this application has acceptable user acceptance, has a good rating, and grade C.